RonPurewal Wrote:First you want to make sure that you understand the basics of what the square/square root combination is doing.
Consider just the expression √(x^2); forget the (y - 4) for now.
* If you plug a positive number in for x, you'll get the same number back out. (Try plugging in a few numbers if you don't already see this.)
* If you plug a negative number in for x, you'll get the opposite number (i.e., made positive) back out.
In other words, √(x^2) is the same as ...
... x itself, if x is positive;
... -x (which is a positive number!), if x is negative.
If x = 0, then √(x^2) = x and √(x^2) = -x are both true statements.
So there's the relationship.
More generally, this means ...
... √(stuff^2) = stuff, if the "stuff" is positive;
... √(stuff^2) = opposite of the stuff, if the "stuff" is negative.
If the stuff is 0, then both of these are true.
Taking that last case into account, the most general form of this fact is:
* √(stuff^2) = stuff --> means the stuff ≥ 0.
* √(stuff^2) = opposite of the stuff --> means the stuff ≤ 0.
If "the stuff" is y - 4, then 4 - y is the opposite of that stuff.
So...
* √((y - 4)^2) = y - 4 means y - 4 ≥ 0, or, in other words, y ≥ 4.
* √((y - 4)^2) = 4 - y means y - 4 ≤ 0, or, in other words, y ≤ 4.
Hope that helps.
Ron, thank you for the explanation, this is beginning to make sense to me, you have an amazing ability to explain tough problems in a digestible way.
I just have one question or issue I hope you can explain/relate to your explanation above:
In chapter 2 of the Algebra workbook we are taught how to solve Absolute Value Equations by "considering both cases." Specifically, we are told that to "Solve for n, given that |n+9|-3n = 3" we can simply set n + 9 = 3 + 3n which gives us n = 3 AND THEN we can set n + 9 = -(3 + 3n) which gives us n = -3.
So following this example, I applied this approach to this problem. Knowing that √x^2 = |x| I went ahead with √((y - 4)^2) as if it were the same thing as |y -4|.
I then went ahead to solve and set y-4 = 4 - y (getting answer y = 4) and then set y - 4 = (-4 - y) (getting no answer) Thus, I moved on to the answer choices with this new equation in mind. Looking for "Is y = 4."
Final answer E.
Can you explain why this approach is the incorrect one to follow from problems such as this one? I understand the logic behind your answer but there is something I am missing because my natural approach would be to follow what I was taught in Chapter 2.